Religious Marketing Communication Approach in Brand Activation Strategy in Islamic Products - Erlan Gantira; Widia Ningsih (Syntax Corporation Indonesia, 2026)
The rapid growth of the halal industry and rising religious awareness among Muslim consumers have pushed companies to move beyond purely commercial marketing toward strategies that also address consumers’ spiritual values, known as Religious Marketing Communication. Although prior studies confirm that religiosity shapes halal purchase intention and consumer trust, none have specifically examined how religious values are operationalized within brand activation strategies for Islamic and halal products, particularly in Indonesia. This study analyzes the concept of Religious Marketing Communication, examines its relevance to brand activation in Islamic and halal products, and describes its implementation strategies. A qualitative library research method was used, analyzing secondary data from books and journal articles through content analysis. Findings show that effective brand activation depends on authentic, ethical communication aligned with sharia principles, supported by storytelling, community empowerment, responsible digital engagement, and consistency between brand messages and business practices; religiosity also influences purchasing decisions, trust, message effectiveness, and loyalty, while inauthentic use of religious symbols risks consumer backlash. These findings contribute theoretically to marketing communication literature and offer practical guidance for marketers and halal industry regulators. In conclusion, Religious Marketing Communication is a strategic approach for building authentic, long-term brand-consumer relationships through the integration of spiritual and ethical values.